Aesthetics and morality - Schellekens, Elisabeth (Continuum aesthetics, 2007)
In this stimulating, lucid and insightful inquiry, philosopher Elisabeth Schellekens invites readers to reflect on their own opinions about art and morality.Aesthetic and moral value are often seen to go hand in hand. They do so not only practically, such as in our everyday assessments of artworks that raise moral questions, but also theoretically, such as in Kant's theory that beauty is the symbol of morality. Some philosophers have argued that it is in the relation between aesthetic and moral value that the key to an adequate understanding of either notion lies. But difficult questions abound. Must a work of art be morally admirable in order to be aesthetically valuable? How, if at all, do our moral values shape our aesthetic judgements - and vice versa?"Aesthetics and Morality" is a stimulating and insightful inquiry into precisely this set of questions. Elisabeth Schellekens explores the main ideas and debates at the intersection of aesthetics and moral philosophy. She invites readers to reflect on the nature of beauty, art and morality, and provides the philosophical knowledge to render such reflection more rigorous. This original, inspiring and entertaining book sheds valuable new light on a notably complex and challenging area of thought."The Continuum Aesthetics" series looks at the aesthetic questions and issues raised by all major art forms. Stimulating, engaging and accessible, the series offers food for thought not only for students of aesthetics, but also for anyone with an interest in philosophy and the arts.